Penerapan Metode Team Quiz dalam Meningkatkan Prestasi Belajar Sejarah Kebudayaan Islam: (Studi Kasus di Madrasah Ibtidaiyah Muawanah Al-Hasyimiyah Dukuhmojo Mojoagung Jombang) - Eny Fatimatuszuhro Pahlawati; Eko Hadi Wardoyo (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2023)
This study aims to determine the increase in student learning values using the Quiz Team Method in realizing active and creative students in Islamic Cultural History Learning at Madrasah Ibtidaiyah Mu'awanah Al-Hasyimiyah Dukuhmojo Mojoagung Jombang.This research is qualitative with a descriptive approach. Data collection was carried out through interviews, observation, documentation and pretest to 29 Class III students. While data analysis was carried out using the Team Quiz method to find out whether there was an increase in student achievement in learning Islamic Cultural History at Madrasah Ibtidaiyah Mu'awanah Al-Hasyimiyah Dukuhmojo Mojoagung Jombang.The results showed that in the pre-cycle of 29 students there were 8 students who had completed and 21 students who had not completed. In cycle I of 29 students only 13 students completed and 16 students had not completed. Then in cycle II there was a slight increase from 29 students, namely 17 students who had completed and 12 students who had not completed. Then in the third cycle of 29 students only 3 students who have not completed and 26 students have completed.